Adjuvant pharmacological and surgical therapy for testicular torsion: Current state of the art. Issue 6 (December 2020) - Thaker, Hatim; Nelson, Caleb P.
Summary: Introduction: Although the consequences of testicular torsion (TT) have been recognized for centuries, little progress has been made to improve outcomes beyond those seen with timely scrotal exploration. Even with testicular salvage, ischemia/reperfusion injury cause significant atrophy and functional impairment. Recent efforts have sought to identify adjuvant pharmacological or surgical interventions that may attenuate these consequences. In this review, we assess the evidence supporting clinical use of these nascent interventions. Methods: We conducted a review of the literature published from 2000 to 2020, using the search terms "torsion", "testicular", "reperfusion", "ischemia", and "injury". Clinical and laboratory research focused on adjuvant pharmacological and surgical techniques mitigating torsion-associated injury in animal models and humans were identified. We recorded intervention timing/dose/route, and outcome timing/category through biomarkers of reperfusion injury, histology, and hormonal/reproductive function. Results: Fifty-four FDA-approved agents, plus 52 herbal/investigational drugs, were reported in animal TT models. In every study, the investigated agents showed beneficial effects on measured endpoints compared to controls. Despite these universally promising animal findings, no pharmacological trials in humans were reported. Surgical techniques studied in animal models included decompression (tunica albuginea incision, TAI), "ischemic conditioning", and hypothermia. Only three human studies on surgical adjuvant maneuvers have been reported, all involving TAI; these showed potential benefit, but the level of evidence is low. Conclusion: There is preliminary evidence that adjuvant treatments may mitigate the effects of ischemia/reperfusion injury. However, the pool of investigated pharmacological agents is wide, yet remarkably shallow; most compounds have been reported in a single animal study. To advance this field, a mechanism-based approach should be used to select promising agents that can be tested systematically. This will determine treatment parameters that maximize safety, efficacy, and tolerability. Only then is it possible to move toward human trials. Adjuvant surgical methods such as TAI show promise in humans but require more robust clinical evaluation.